Role of the parents and the social environment in the achievement of pencak silat athletes of perguruan bina mental of special region of Yogyakarta - Agung Sentosa; Syamsuryadin, Syamsuryadin; Adinda Putri Agustina; Jihan Salmah Oktiga; Agris Nadia Putri; Aniy Vaynah Fikratul Iliyyi; Ahya Mulya Bhakti; Intan Dwi Rahmawati; Nia Popdanawati; Hanif Rahmawan; Idul Wibowo (Jorpres (Jurnal Olahraga Prestasi), 2024)
This research aims to: (1) determine the correlation between the role of parents in the achievement of pencak silat athletes of Perguruan Bina Mental Yogyakarta (Bina Mental Yogyakarta Dojo); (2) figure out the correlation between the role of the social environment in the achievement of pencak silat athletes of Perguruan Bina Mental Yogyakarta; and (3) find out the correlation between the role of parents and the social environment in the achievement of pencak silat athletes of Perguruan Bina Mental of Special Region of Yogyakarta. This research was a descriptive study with survey method. The research population was Pencak Silat athletes from Perguruan Bina Mental Yogyakarta, totaling 30 athletes. The sampling technique used total sampling. The research instrument used a questionnaire. The data analysis used simple linear regression analysis and multiple linear regression. The results of the research show that: (1) there is a correlation between the role of parents in the achievement of pencak silat athletes of Perguruan Bina Mental Yogyakarta; (2) there is a correlation between the role of the social environment in the achievement of pencak silat athletes of Perguruan Bina Mental Yogyakarta; and (3) there is a correlation between the role of parents and the social environment in the achievement of pencak silat athletes of Perguruan Bina Mental Yogyakarta.